Analysis of The Implementation Quantum Teaching Method in Teaching English at Five Grade of SDN Bakalrejo 2 in The Academic Year 2016/2017 - Sandy Yoga Nauri (Universitas Islam Lamongan, 2017)
This research was aimed to analisys implementation of quantum teaching method in teaching English at five grade SDN Bakalrejo 2 academic year 2016/2017 and the problems found in the implementation of quantum teaching method in teaching english at five grade SDN Bakalrejo 2 academic year 2016/2017. This research method is qualitative research. The type of research is descriptive approach. In this study, the types and sources of data used are interview result, field observation results, and data about informants. Data collection methods used in this study include: interview and observation. is through data reduction process, data presentation, and conclusion drawing. The Result research are in the application of Quantum Teaching method in SDN Bakalrejo 2. There are several impacts of the application of Quantum Teaching Method, namely, the spirit and pleasure of students in learning. The problem of implementation Quantum Teaching method providing students with an understanding of the purpose of the lesson and the material being taught, as the ability of each student to understand is different. Furthermore, it provides a stimulation or example of the material to be conveyed. It is also difficult to find relevant media in learning.Keywords: Quantum Teaching, Implementation Quantum Teaching, Problem of Quantum Teaching